2014
DOI: 10.1186/1471-2458-14-436
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of objectively measured overweight/obesity and physical activity in Kenyan school children: results from ISCOLE-Kenya

Abstract: BackgroundChildhood overweight/obesity and inadequate physical activity burden Western countries, and now, pose a growing threat to the health of children in low and middle income countries. Behavioural transitions toward more sedentary lifestyles coupled with increased consumption of high calorie foods has resulted in rising proportions of overweight/obesity and decreasing levels of physical activity in school-aged children. The objective of this study was to determine the prevalence and to investigate factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
98
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 39 publications
17
98
2
3
Order By: Relevance
“…The ISCOLE-Kenya study found that only one-half of the participating schools offered organized soccer, volleyball, track and field, and swimming to the children and youth. 20 Although Kenya is a sporting nation having achieved considerable success in athletics and rugby, only about half of schools studied offered organized sports that allow children's participation. 20 Provision of sufficient sports facilities both in school and at the community level is key as facilities normally attract children and youth to participate in PA.…”
Section: Organized Sport Participation: Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The ISCOLE-Kenya study found that only one-half of the participating schools offered organized soccer, volleyball, track and field, and swimming to the children and youth. 20 Although Kenya is a sporting nation having achieved considerable success in athletics and rugby, only about half of schools studied offered organized sports that allow children's participation. 20 Provision of sufficient sports facilities both in school and at the community level is key as facilities normally attract children and youth to participate in PA.…”
Section: Organized Sport Participation: Cmentioning
confidence: 99%
“…20 Although Kenya is a sporting nation having achieved considerable success in athletics and rugby, only about half of schools studied offered organized sports that allow children's participation. 20 Provision of sufficient sports facilities both in school and at the community level is key as facilities normally attract children and youth to participate in PA. There are different factors that motivate Kenyans to participate in organized sports and physically active children and youth have better academic performance, body image, leadership qualities, and an element of team spirit than those who do not participate in sports.…”
Section: Organized Sport Participation: Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 studies estimated proportions of children meeting global PA guidelines. 11,13,15 Based on a weighting of these findings, it was estimated that about one-half of Kenyan children and adolescents met the global PA guideline. Accelerometry data also show that urban children and adolescents had significantly lower MVPA than rural peers.…”
Section: Discussionmentioning
confidence: 99%
“…ISCOLE-Kenya showed that maternal and paternal education level and total annual household income were associated with meeting recommended PA guidelines, 15 with a decreasing trend in the number of children who met the guidelines with increasing maternal/paternal educational attainment and increasing household SES. A study on a pastoralist community 17 noted gender differences in the encouragement and acceptability of, or participation in PA. Certain sociocultural beliefs do exist in some Kenyan communities whereby female children are discouraged from being physically active-a trait deemed unfeminine.…”
Section: Discussionmentioning
confidence: 99%